Influence of Storage Condition and Period Time on Fungal Contamination and Mycotoxin in Ruminant Feed - Hamasalim, Hozan Jalil; Ahmed, Bahroz Muhammed Saleh; Mohammed, Shagul Jalal (Jordan Journal of Agricultural Sciences, 2021)
Contamination of animal feeds with mycotoxins in livestock farms is a severe matter. This study aimed to evaluate mycotoxigenic fungi, type of toxins, and toxin concentrations and contamination levels of Aflatoxin, Ochratoxin, and T2-toxin in ruminant feed collected from three different sites (a department laboratory, field 1, and field 2) and two periods of time (January and March). Also, four different genera were isolated and diagnosed from the animal feed based on the macroscopic morphology as well as on microscopic characteristics. The genera were Aspergillus spp., Penicillium spp., Fusarium spp., and Rhizopus spp. The result shows significant differences in fungal count among location storages, and among period times, too. Significant differences (P<0.05) also has found for mycotoxin concentration while storage in different locations. Additionally, animal feed collected from different sites and different periods contained lower limits of mycotoxins than the standard limits.